2021
DOI: 10.3390/vaccines10010036
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of Racial Differences in COVID-19 Vaccine Acceptance and Uptake: A Cohort Study in Detroit, MI

Abstract: Despite their disparate rates of infection and mortality, many communities of color report high levels of vaccine hesitancy. This paper describes racial differences in COVID-19 vaccine uptake in Detroit, and assesses, using a mediation model, how individuals’ personal experiences with COVID-19 and trust in authorities mediate racial disparities in vaccination acceptance. The Detroit Metro Area Communities Study (DMACS) is a panel survey of a representative sample of Detroit residents. There were 1012 responden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
3
10
0
Order By: Relevance
“…However, differences in receiving an offer cannot fully explain the disparities in vaccination uptake. Unadjusted survey results show lower vaccination rates for migrants as compared to non-migrants among those offered a vaccine (79.9% vs. 91.1%), which is consistent with register data from Norway [9] and research in other countries regarding low vaccination uptake among migrants and ethnic minorities [21]. Nonetheless, our results suggest that issues associated with the necessary precondition of being offered a vaccine also play a role in observed vaccination differences.…”
Section: Discussionsupporting
confidence: 88%
“…However, differences in receiving an offer cannot fully explain the disparities in vaccination uptake. Unadjusted survey results show lower vaccination rates for migrants as compared to non-migrants among those offered a vaccine (79.9% vs. 91.1%), which is consistent with register data from Norway [9] and research in other countries regarding low vaccination uptake among migrants and ethnic minorities [21]. Nonetheless, our results suggest that issues associated with the necessary precondition of being offered a vaccine also play a role in observed vaccination differences.…”
Section: Discussionsupporting
confidence: 88%
“…Research conducted in Detroit indicated that if NH Black Americans had similar confidence levels in healthcare providers as NH White Americans, 23% of the gap in vaccination uptake could be eliminated. A similar finding was reflected in the level of trust in government between Black and White Detroiters [ 22 ]. Structured racism significantly impacts health education programs that aim to increase patient trust in the medical system.…”
Section: Discussionsupporting
confidence: 68%
“…For instance, Black Americans had a 1.7-times-higher mortality rate, a 2.2-times-higher risk of being hospitalized, and a 1.1-times-higher chance of receiving a COVID-19 diagnosis than NH white Americans as of November 2022 [ 49 ]. This COVID-19 disparity further exacerbated the mistrust and vaccine hesitancy; some researchers found out that, by race/ethnicity, there were substantial differences in healthcare provider trust, and if NH Black Detroiters had levels of healthcare provider confidence comparable to those of NH white Detroiters, 23% of the differences in vaccination uptake by race could be removed [ 50 ].…”
Section: Discussionmentioning
confidence: 99%